Simultaneous detection of Legionella species and Legionella pneumophila by duplex PCR (dPCR) assay in cooling tower water samples from Jakarta, Indonesia (Medical Journal of Indonesia, 2010)
Aim: Since culture method is time-consuming and has low sensitivity, we developed a duplex PCR (dPCR) assay for the detection of Legionella sp. and L. pneumophila in cooling tower samples. We used culture method as a gold standard. Methods: Optimization of dPCR method was performed to obtain an assay with high sensitivity and specifi city. The optimized method was used to detect Legionella sp. dan L. pneumophila in 9 samples obtained from 9 buildings in Jakarta. For culture method, the bacteria were grown or isolated on selective growth factor supplemented-buffered charcoal yeast extract (BCYE) media. Results: Of 9 samples tested by dPCR assay, 6 were positive for Legionella species,1 was positive for L. pneumophila, and 2 showed negative results. For the same samples, no Legionella sp. was detected by the culture method. Conclusion: dPCR assay was much more sensitive than the culture method and was potentially used as a rapid, specifi c and sensitive test for routine detection of Legionella sp. dan for L. pneumophila in water samples. (Med J Indones 2010; 19:223-7)